2015
DOI: 10.1016/j.asjsur.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of prophylactic cefazolin in the prevention of infection after various types of abdominal wall hernia repair with mesh

Abstract: Preoperative administration of single-dose cefazolin for prosthetic hernia repairs did not markedly decrease the risk of wound infection. Our results do not support the use of cefazolin as a prophylactic antibiotic for various kinds of abdominal wall hernia repair with mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Of these, 195 unique articles were selected by title or abstract data; 98/195 of these did not meet the inclusion criteria. This left a total of 99 articles for evaluation: 34 from Asia (Austin et al, 2004;Duerink et al, 2006;Kanafani et al, 2006;Wu et al, 2006;Ali et al, 2009;Buang and Haspani, 2012;Ee et al, 2014;El Beltagy et al, 2010;Khan et al, 2010Khan et al, , 2011Lee et al, 2007Lee et al, , 2010Lee et al, , 2015Malik et al, 2009;Mathur et al, 2013;Memon et al, 2013;Nausheen et al, 2013;Sangrasi et al, 2008;Saramma et al, 2011;Akhter et al, 2016;Al-Mulhim et al, 2014;Bibi et al, 2015;Hey et al, 2017;Jyothirmayi et al, 2017;Mehrabi Bahar et al, 2015;Mundhada and Tenpe, 2015;Ng et al, 2015;Pardhan et al, 2013;Sahu et al, 2016;Shah et al, 2015Shah et al, , 2017Singh et al, 2015;Vaze et al, 2014;Yu et al, 2015), 27 from LATAM (Alvarez-Moreno et al, 2014;Bannura et al, 2016;Barbosa et al, 2004;Bellusse et al, 2015;da Cunha et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 195 unique articles were selected by title or abstract data; 98/195 of these did not meet the inclusion criteria. This left a total of 99 articles for evaluation: 34 from Asia (Austin et al, 2004;Duerink et al, 2006;Kanafani et al, 2006;Wu et al, 2006;Ali et al, 2009;Buang and Haspani, 2012;Ee et al, 2014;El Beltagy et al, 2010;Khan et al, 2010Khan et al, , 2011Lee et al, 2007Lee et al, , 2010Lee et al, , 2015Malik et al, 2009;Mathur et al, 2013;Memon et al, 2013;Nausheen et al, 2013;Sangrasi et al, 2008;Saramma et al, 2011;Akhter et al, 2016;Al-Mulhim et al, 2014;Bibi et al, 2015;Hey et al, 2017;Jyothirmayi et al, 2017;Mehrabi Bahar et al, 2015;Mundhada and Tenpe, 2015;Ng et al, 2015;Pardhan et al, 2013;Sahu et al, 2016;Shah et al, 2015Shah et al, , 2017Singh et al, 2015;Vaze et al, 2014;Yu et al, 2015), 27 from LATAM (Alvarez-Moreno et al, 2014;Bannura et al, 2016;Barbosa et al, 2004;Bellusse et al, 2015;da Cunha et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
“…,Gao et al (2010),Gil-Londoño et al (2016),Giri et al (2008),Hafez et al (2012),Hao et al (2013),Hernaiz-Leonardo et al (2017),Hey et al (2017),Ibrahim et al (2014),Jyothirmayi et al (2017),Kanafani et al (2006),Khan et al (2010),Khan et al (2011),Ledur et al (2011),Lee et al (2007),Lee et al (2010),Lee et al (2015),Legesse Laloto et al (2017),Leon et al (2011),Li et al (2013),Liu et al (2017),Lyimo et al (2013),Madu et al (2011), El Maerrawi and Carvalho (2015),Malik et al (2009),Martins et al (2008),Marwa et al (2015),Mathur et al (2013),Mawalla et al (2011),Mehrabi Bahar et al (2015),Memon et al (2013),Mundhada and Tenpe (2015),Nagaya et al (2017),Ng et al (2015),Ning et al (2014),Nwankwo and Edino (2014),Oliveira and Carvalho (2004),Pardhan et al (2013), Porras-Hernandez et al (2008,Portillo-Gallo et al (2014),Qi et al (2013),Qin et al (2014),Qiu et al (2011),Rabiu ...…”
mentioning
confidence: 99%
“…Moreover, in a prospective randomized control study evaluating wound infection rates in 395 patients with various types of hernia undergoing elective mesh repair, 237 patients (60.0%) received prophylactic cefazolin (study group), while the remaining 158 patients (40.0%) did not receive any prophylactic antibiotics (control group) [ 29 ]. Patients were monitored for infections at multiple intervals postoperatively, including at 10 days, 30 days, 12 months, and annually for at least two years.…”
Section: Reviewmentioning
confidence: 99%
“…Patients were monitored for infections at multiple intervals postoperatively, including at 10 days, 30 days, 12 months, and annually for at least two years. The results revealed that eight patients (2.03%) experienced infection at the surgical site, with two (1.27%) occurring in the control group and six (2.53%) in the study group, suggesting that preoperative administration of single-dose cefazolin for prosthetic hernia repairs did not markedly decrease the risk of wound infection [ 29 ]. Similarly, in a prospective, randomized, double-blind trial involving 450 patients undergoing primary inguinal hernia repair electively using polypropylene mesh, analysis of 334 out of the 450 patients who completed a one-month follow-up period revealed that the overall infection rate was 8.7% (29 out of 334), with a wound infection incidence of 7% in the antibiotic group and 10.5% in the control group.…”
Section: Reviewmentioning
confidence: 99%
“…The microbiological cultured in these two cases showed infection by Staphylococcus aureus and by Pseudomonas aeruginosaalso in the second case. S. aureus [198] and Staphylococcus epidermidis [199] are the most common microorganisms related to mesh infection (approximately 90%), S. aureus (MRSA) [200], involved in up to 63% of surgical site mesh-related infections [201][202][203], being methicillin-resistant. Other microorganisms related to mesh infection include Streptococcus pyogenes [204], Enterococcus faecalis [205,206], Pseudomonas sp.…”
Section: Chronic Mesh Infection Problemmentioning
confidence: 99%